Pengaruh Customer Intimacy, Kualitas Produk & Layanan Terhadap Loyalitas Nasabah Bank Syariah Indonesia: Studi Kasus Bank Syariah Indonesia Cabang Tangerang Selatan - Hulu, M. Rizki Hanif; Lubis, Irsad (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2025)
This study aims to determine the effect of Customer Intimacy, Product Quality and Service on Customer Loyalty at Bank Syariah Indonesia in the South Tangerang area. This research uses descriptive quantitative method. The population of this research is the customers of Bank Syariah Indonesia who live in South Tangerang. The sample technique used is simple random sampling of 100 people. Data collection techniques using questionnaires were analyzed using simple linear regression, multiple, T test, F test, and the coefficient of determination. The results of this study indicate that: (1) There is no positive and significant effect of the customer intimacy variable on customer loyalty at Bank Syariah Indonesia in the South Tangerang area; (2) There is no positive and significant influence of product quality variables on customer loyalty of Bank Syariah Indonesia in the South Tangerang area; (3) There is a positive and significant influence of service quality variables on customer loyalty of Bank Syariah Indonesia in the South Tangerang area; (4) There is a positive and significant influence of customer intimacy, product quality, service quality on customer loyalty of Bank Syariah Indonesia in the South Tangerang area.